Determination of rate coefficients and diffusion coefficients of butanol using RF-GC methodologies - Khalid, K.; Zain, Sharifuddin Md; Khan, R.A. (2011)
Reversed-flow gas chromatography, which is a sub-technique of inverse gas chromatography, is an experimental arrangement simulating a simple model for the action of liquid pollutants in laboratory scale. By using a commercial gas chromatograph and an appropriate mathematical analysis, kinetic parameters such as rate coefficients, kc and diffusion coefficients, D of analyzed liquid were calculated. These physicochemical properties of the liquid experimented will contribute to the references for future research in the area of environment, food, agriculture as well as physical sciences.